A professional approach Microsoft Office Access 2003 comprehensive - Juarez, Jon; Carter, John; Stewart, Kathleen (Boston McGraw-Hill technology Education, 2005)
Understanding Access databases; Designing and managing database objects; Integrating database objects; Using advanced features.
Includes index
Keywords: Database management; Microsoft Access; Tin học